3M syndrome with novel CUL7 variants in a Chinese patient: a case report - Liu, Hui; Liu, Gaojie; Suo, Weicai; Han, Shuaishuai; Wang, Yizhong; Ding, Hongfang (Frontiers in Pediatrics, 2025)
Background3M syndrome is a rare autosomal recessive disorder caused by biallelic pathogenic variants in the cullin 7 (CUL7), obscurin-like 1 (OBSL1), and coiled-coil domain-containing protein 8 (CCDC8) genes and is characterized by pre- and postnatal growth retardation, short stature, dysmorphic facial features, and skeletal anomalies, with normal intelligence.Case presentationIn this study, we report a 6-year-old female patient from China diagnosed with 3M syndrome. The patient presented with typical clinical features of growth retardation and short stature, with normal intelligence. The patient’s dysmorphic facial features included relative macrocephaly, a protruding forehead, a triangular face, a pointed chin, a flat nasal bridge, full lips, a long philtrum, and a broad lower jaw. The skeletal survey was normal except for clinodactyly of the fifth fingers of both hands. Growth hormone (GH) deficiency was excluded by normal serum hormone levels and the GH stimulation test results. Whole-exome sequencing identified two heterozygous variants in CUL7, NM_014780.5: c.1639_1640del (p.Leu547Alafs*6), and NM_014780.5: c.4505T>C (p.Ile1502Thr). Parental Sanger sequencing confirmed these as compound heterozygous variants, with one variant inherited from each parent. Neither variant has been previously reported. The patient has been treated with recombinant human IGF-1 for 2 years since she was 4 years old and has achieved a growth velocity of approximately 6–7 cm per year.ConclusionsHerein, we describe a Chinese patient with 3M syndrome caused by novel biallelic pathogenic variants in CUL7 from a non-consanguineous family, expanding the genetic spectrum of CUL7 in the Chinese population.